2021
DOI: 10.1016/j.avsg.2021.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Thrombosis in the Course of Covid-19 Disease; Two Rare Cases

Abstract: Objective Acute aortic thrombosis and floating aortailiac thrombus are infrequent clinical conditions with high morbidity and mortality rates. It was observed that; SARS-CoV-2 coronavirus disease (Covid-19) caused a hyperinflammation and hyperimmune state and these conditions can result in a hypercoagulation and eventually thrombotic events might occur. Methods Here we presented two covid-19 positive patients with rare aortic thrombotic events. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Importantly, our case demonstrated that the functional asplenia may persist even months after the acute phase of splenic infarct highlighting the need for continuous antibiotic treatment, correct administration of vaccines and vigilance for potential infections. Aortic thrombosis, another complication rarely seen in the acute COVID-19 sequelae [ 7 , 19 , 20 ] was also reported at our patient and was attributed to severe COVID-19 pneumonia inducing prothrombotic state through one of the aforementioned mechanisms. Notably, antiphospholipid antibodies frequently seen in other cases with arterial thrombotic complications were not detected in our patient, nor were anticardiolipin antibodies that could partially explain the acquired coagulopathy in this patient [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 65%
“…Importantly, our case demonstrated that the functional asplenia may persist even months after the acute phase of splenic infarct highlighting the need for continuous antibiotic treatment, correct administration of vaccines and vigilance for potential infections. Aortic thrombosis, another complication rarely seen in the acute COVID-19 sequelae [ 7 , 19 , 20 ] was also reported at our patient and was attributed to severe COVID-19 pneumonia inducing prothrombotic state through one of the aforementioned mechanisms. Notably, antiphospholipid antibodies frequently seen in other cases with arterial thrombotic complications were not detected in our patient, nor were anticardiolipin antibodies that could partially explain the acquired coagulopathy in this patient [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 65%
“…A total of 55 patients from the database research and 1 patient from our facility were included. 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 Of the included studies, 12 were case series and 26 were case reports. Essential characteristics of the included patients are outlined in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“… 6 , 7 One of these cases regarded a 55-year-old male who presented with renal infarction and lower limb ischemia 6 and was managed with Fogarty embolectomy and anticoagulation. In the second case 7 a 74-year-old female presented with a dramatic clinical picture of aortic barrage but died before any treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature a total of 6 cases of AFT involving the abdominal aorta have already been described, 49 2 of them in patients who had a concomitant COVID-19 infection. 6,7 One of these cases regarded a 55-year-old male who presented with renal infarction and lower limb ischemia 6 and was managed with Fogarty embolectomy and anticoagulation. In the second case 7 a 74-year-old female presented with a dramatic clinical picture of aortic barrage but died before any treatment.…”
Section: Discussionmentioning
confidence: 99%